Universal health coverage in India and health technology assessment: current status and the way forward - Lahariya, Chandrakant; Sahoo, Krushna Chandra; Sundararaman, T.; Prinja, Shankar; Rajsekhar, Kavitha; Pati, Sanghamitra (Frontiers in Public Health, 2023)
In India, there is a renewed emphasis on Universal Health Coverage. Alongside this, Health Technology Assessment (HTA) is an important tool for advancing UHC. The development and application of HTA in India, including capacity building and establishing institutional mechanisms. We emphasized using the HTA approach within two components of the Ayushman Bharat programme, and the section concludes with lessons learned and the next steps. The UHC has increased the importance of selecting and implementing effective technologies and interventions within national health systems, particularly in the context of limited resources. To maximize the use of limited resources and produce reliable scientific assessments, developing and enhancing national capacity must be based on established best practices, information exchange between different sectors, and collaborative approaches. A more potent mechanism and capacity for HTA in India would accelerate the country's progress towards UHC.